ANALISIS AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN KEUANGAN DESA LANGKOMU KECAMATAN MAWASANGKA TENGAH KABUPATEN BUTON TENGAH - Rais R, Muhammad (JIM : Journal Of International Management, 2023)
This study aims to analyse the Accountability and Transparency of Financial Management based on Permendagri No. 113 of 2014. The data analysis method is descriptive qualitative. The results of the study are (1) Accountability of the financial management planning stage where its application has been allocated and guided by Permendagri No. 113 of 2014. Evidenced by the Raperbedes APBDesa which was discussed between the village government and the Village Consultative Body (BPD) in the village deliberation forum. (2) Transparency of village financial management in Langkomu village for its application is in accordance with Permendagri No. 113 of 2014, the existence of information notice boards or billboards in each hamlet and village accountability reports reported to the Regent / Mayor through the Camat. (3) The reporting and accountability stage of the APBDesa Realisation Accountability Report in Langkomu village has used the realisation accountability report format and has been guided by Permendagri No. 113 of 2014, namely the village has reported the realisation of semester I and II, as well as an accountability report on the realisation of the APBDesa implementation at the end of the fiscal year.